Gender roles of Polish female emigrants and their paths of self-realization in relation to work-life balance policy - Zalewska-Łunkiewicz, Karolina; Zygmunt, Agata (Political Preferences, 2018)
A numerous previous reports on Polish women’s emigration provided information on their passive role in the decision making process concerning leaving Poland, obtaining employment predominantly in the sector of household services or their marriage-oriented strategy of survival in the foreign country. The current picture of women’s roles in emigration has been changed. The purpose of the presented research was to explore the paths of self-realization of Polish female emigrants regarding the gender roles realised by them in the field of the work-life balance idea. The research was conducted in psycho-sociological approach. There were 113 adult Polish female emigrants, who had spent a period of time exceeding one year on emigration in Europe, North America, Australia and Asia admitted to the research. This project was realised on the basis of quantitative data gathered throughout online survey and supplemented by qualitative data in the shape of 15 semi-structured interviews. The obtained results showed that the examined Polish women declare to undertake gender roles compliant with the new cultural model, and to lesser extent compliant to the traditional one. They demonstrated proactiveness in the phase of decision-making about emigration and as they attempted to combine their family life with the professional sphere in the country they have arrived in what corresponds with the WLB idea promoted in developed countries. Key words: work-life balance, gender roles, self-realization, Polish women, emigrants